A New Perspective on the Role of Self-Confidence and Confidence in the Evaluation and Rehabilitation of Children With Adverse Life Experience and Borderline Intellectual Functioning: A Preliminary Study - Valle, Annalisa; Baglio, Gisella; Zanette, Michela; Massaro, Davide; Baglio, Francesca; Marchetti, Antonella; Blasi, Valeria (Frontiers in Psychology, 2021)
The Borderline Intellectual Functioning (BIF) is a neurodevelopmental condition characterized by a borderline intelligence quotient (range 70-85), with difficulties in cognitive and social domains. Children with BIF often live in adverse conditions and show academic and behavioral difficulties. Rehabilitation programmes for these children focus mainly on cognitive aspects, sometimes with the aid of new technologies able to engage and motivate. In this framework, the affective development of children with BIF, and its possible role on the difficulties they manifest and in the rehabilitation is still poorly investigated. In this work we investigate the characteristics of the internal working models of these children applying the Separation Anxiety Test, using both the classical and a new qualitative coding system to identify the specific features of the attachment representation. Results delineate a profile characterized by low-self-confidence and high separation anxiety, with a tendency to somatization. In the light of these results, we suggest that this attachment profile impacts on the therapeutic relationships and on the efficacy in the use of the technological devices. We propose a new perspective in which the interpersonal relationship with the psychologist and the support of children’s self-confidence is crucial to treat cognitive and behavioral difficulties in children with BIF: only in this case, the use of new technologies and tools may be effective in promoting the greatest possible benefit from therapeutic interventions.